Exploring first-year engineering student perceptions of peer-led study groups in a Global South context (Journal of Student Affairs in Africa, 2024)
The purpose of the study is to explore the advantages of study groups for first-year engineering students in a challenged Global South context. The research aims to explore how the support and resources provided by the peer-led study groups can help students cope with the stressors and challenges that are often associated with the transition to university and the demands of an engineering programme. Educational institutions prioritise student development, yet many studentinitiatives overlook student agency and that understanding students’ learning approaches is necessary for effective support initiatives. A total of 40 registered engineering students, who voluntarily enrolled in the peer-led study groups, were the subjects of this study at the University of Pretoria. The research adopted a qualitative approach and aimed to explore the advantages of study groups. Data were collected through interviews and surveys with both students and study group leaders to gain their respective views on the strengths and areas for improvement of the learning community experience. The research was conducted using qualitative methods to gain a deeper understanding of students’ experiences with study groups and the associated benefits. Through participation in study groups, students benefited from the support of their peers, opportunities for alternative problem solving methods, and improved academic performance. Furthermore, the smaller group size and collaborative nature of these groups created a supportive and empowering learning environment, where students felt confident to ask questions and engage in meaningful learning opportunities.